Absolute beginner's guide to computer basics - Miller, Michael, 1958- (Que, 2005)
Pt. I. Getting started -- 1. Understanding your PC hardware -- What your computer can, and can't, do -- Getting to know your personal computer system -- Computer hardware basics -- 2. Setting up your new computer system -- Before you get started -- Connecting the cables -- Turning it on and setting it up -- pt. II. Using Windows -- 3. Understanding Microsoft Windows XP -- What Windows is, and what it does -- Different versions of Windows -- Working your way around the desktop -- Important Windows operations -- Using the start menu -- Understanding files and folders -- All the other things in Windows -- Getting help in Windows -- 4. Taking Windows for a spin -- Playing a game -- Launching a program, and printing and saving a document -- Viewing your documents -- Examining your hard disk -- Shutting down your system -- 5. Personalizing Windows -- Changing the look of your desktop -- Organizing desktop icons -- Changing the way the start menu works -- Activating special effects -- Changing your click -- Using a screensaver -- Resetting the time and date -- Setting up additional users -- 6. Working with files and folders -- Viewing folders and files -- Navigating folders -- Creating new folders -- Renaming files and folders -- Copying files -- Moving files -- Deleting files -- Working with compressed folders -- pt. III. Upgrading and maintaining your system -- 7. Adding new hardware and devices to your system -- Most popular peripherals -- Understanding ports -- Adding new external hardware -- Adding new internal hardware -- Using the add hardware wizard -- Connecting portable devices to your PC -- 8. Setting up a home network -- How networks work -- Setting up a wired or wireless network -- Running the network setup wizard -- Setting up wireless security -- Sharing files and folders across the network -- 9. Performing routine maintenance -- Free up disk space by deleting unnecessary files -- Make you hard disk run better by defragmenting -- Perform a hard disk checkup with ScanDisk -- Keep your hardware in.